Following the financial crisis: risk and opportunities for Singapore - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Asian economies are showing signs of recovery, and the stock markets have rebounded, leading to optimism that the worst of the economic crisis is over. However, few are expecting a quick return to the boom years, for weakness still persists in major economies while uncertainties remain in others. Nevertheless, for those Singapore-based regional financial industry players speaking at a recent seminar organised by the Sim Kee Boon Institute of Financial Economics, they are picking up lessons learned, seeing beyond the near-term worries, and finding growth opportunities.